Identifying and Shifting Disempowering Paradigms for Families of Children With Disability Through a System Informed Positive Psychology Approach - Mahmic, Sylvana; Kern, Margaret L.; Janson, Annick (Frontiers in Psychology, 2021)
Despite the emergence of socio-ecological, strengths-based, and capacity building approaches, care for children with disability remains primarily grounded in a deficit-based perspective. Diagnoses and interventions primarily focus on what children and families cannot do, rather than what might be possible, often undermining the competence, mental health, and functioning of both the children and their families. We first critically examine typical approaches to disability care for families of young children, describe the importance of a systems informed positive psychology (SIPP) approach to care, and identify the existence of two dominant paradigms, disability is a disadvantage and experts know best. Then, we present a case study investigating families’ experiences with these two paradigms and whether shifts to alternative perspectives could occur through participation in a SIPP-based program informed co-designed by professionals and families. Of program participants, nine parents and five early intervention professionals participated in two separate focus groups, and ten e-books were randomly selected for review. Thematic analysis of the e-books and focus group data identified two primary themes representing alternative perspectives that arose through the intervention: we will start with our strengths and we’ve got this. Participant comments indicated that they developed a greater sense of hope, empowerment, engagement, and wellbeing, enabled by embedding wellbeing concepts and practices in their routines and communications with their children. We suggest that benefits arose in part from the structure of the program and the development of wellbeing literacy in participants. While care needs to be taken in generalizing the results, the case study provides clear examples of shifts in perspectives that occurred and suggests that the incorporation of SIPP principles within early intervention approaches provides a potential pathway for shifting the problematic paradigms that dominate disability care.